The effect of slow deep breathing exercise on IL-6 and IL-10 levels in hypertensive elderly: a pre-experimental study - Chisholi, Abdillah Choirul (JHeS (Journal of Health Studies), 2026)
Hypertension is a major risk factor for cardiovascular disease and is often associated with chronic inflammatory processes. Pro-inflammatory cytokines such as Interleukin-6 (IL-6) play a role in the pathogenesis of hypertension, whereas anti-inflammatory cytokines such as Interleukin-10 (IL-10) can inhibit inflammatory effects. Slow Deep Breathing Exercise (SDBE) has been linked to improved autonomic nervous system regulation and potential anti-inflammatory effects. This study used a one-group pretest-posttest design involving 35 pre-elderly and elderly participants with hypertension. Subjects underwent SDBE intervention for six weeks, three sessions per week, with each session lasting 10–15 minutes. IL-6 and IL-10 levels were measured using the ELISA method, and blood pressure was measured before and after the intervention. Data analysis was performed using the Wilcoxon Signed Rank Test. There was a significant increase in IL-10 levels after the intervention (p = 0.000), but IL-6 levels showed no significant change (p = 0.108). Systolic and diastolic blood pressure significantly decreased from 158.54±13.86 mmHg to 149.69±13.90 mmHg (p = 0.005) and from 88.80±15.08 mmHg to 84.66±8.99 mmHg (p = 0.005), respectively. In older adults with hypertension, slow deep breathing exercise can lower blood pressure and raise IL-10 levels, an anti-inflammatory cytokine, while IL-6 levels did not significantly change. This intervention can be used as a non-pharmacological therapy to help manage hypertension.